2009
DOI: 10.1038/modpathol.2009.148
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of SALL4 in primary germ cell tumors of the central nervous system: a study of 77 cases

Abstract: Primary germ cell tumors of the central nervous system (CNS) sometimes pose diagnostic difficulty. In this study we analyzed the diagnostic utility of a novel marker, SALL4, in 77 such tumors (59 pure and 18 mixed) consisting of the following tumors/tumor components: 49 germinomas, 7 embryonal carcinomas, 27 yolk sac tumors, 3 choriocarcinomas, and 14 teratomas. We also stained SALL4 in 99 primary non-germ cell tumors to test SALL4 specificity. We compared SALL4 with OCT4 in all germ cell tumors and compared S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 30 publications
4
54
0
Order By: Relevance
“…Other immunohistochemical stains would obviously be useful adjuncts in this differential diagnostic setting. The widely available renal cell carcinoma marker PAX-8 18,19 and the novel germ cell marker SALL-4 [20][21][22] would be useful in an immunohistochemical panel when renal cell carcinoma or a germ cell tumor are considered, respectively. Although no chordomas expressed SALL-4 in this study, 1 of 12 cases had patchy weak nuclear immunoreactivity for PAX-8.…”
Section: Resultsmentioning
confidence: 99%
“…Other immunohistochemical stains would obviously be useful adjuncts in this differential diagnostic setting. The widely available renal cell carcinoma marker PAX-8 18,19 and the novel germ cell marker SALL-4 [20][21][22] would be useful in an immunohistochemical panel when renal cell carcinoma or a germ cell tumor are considered, respectively. Although no chordomas expressed SALL-4 in this study, 1 of 12 cases had patchy weak nuclear immunoreactivity for PAX-8.…”
Section: Resultsmentioning
confidence: 99%
“…Primary extragonadal germ cell tumors are uncommon tumors that most often occur in the midline structures and mediastinum, but they can also occur in many other organs, not only in children but also in adults. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Morphologically, primary extragonadal germ cell tumors can mimic many types of non-germ cell tumors. For example, mediastinal seminomas may mimic type B thymomas and embryonal carcinoma may mimic other types of carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The yolk sac tumor is the extragonadal germ cell tumor that poses the greatest diagnostic challenges because of its multiple histological patterns and wide organ distribution. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Previous markers for diagnosing extragonadal yolk sac tumors included placental-like alkaline phosphatase, a-fetoprotein, and glypican-3, but they lack adequate sensitivity and specificity. Recent studies have shown that SALL4 is a more sensitive marker for primary extragonadal yolk sac tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations